Easy Entry into Reduced Ar‐BIANH2 Compounds: A New Class of Quinone/Hydroquinone‐Type Redox‐Active Couples with an Easily Tunable Potential1. Issue 44 (11th September 2014) - Viganò, Marta; Ferretti, Francesco; Caselli, Alessandro; Ragaini, Fabio; Rossi, Manuela; Mussini, Patrizia; Macchi, Piero
Abstract Ar‐BIANH2 bearing different substituents on the aryl rings have been synthesized in high yield by reduction of the corresponding bis(aryl)acenaphthenequinonediimine (Ar‐BIAN) compounds. The structure of p‐CH3C6H4‐BIANH2 in the solid state was determined by X‐ray diffraction. An exhaustive voltammetric investigation of the two parallel BIAN and BIANH2 series afforded a first rationalization of the redox properties of these molecules, highlighting their analogies with quinone/hydroquinone systems. Such analogies, in combination with the much more negative reduction potential range of Ar‐BIAN compounds with respect to quinones, can afford to extend the range of reduction potentials so far obtainable by the use of quinones.